2014
DOI: 10.1186/1475-2840-13-48
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and 1-hour post-load plasma glucose in hypertensive patients

Abstract: BackgroundA plasma glucose value ≥155 mg/dl for 1-hour post-load plasma glucose during an oral glucose tolerance test (OGTT) is able to identify subjects with normal glucose tolerance (NGT) at high-risk for type-2 diabetes and with subclinical organ damage. We designed this study to address if 25-hydroxyvitamin D [25(OH)D] circulating levels are associated with glucose tolerance status, and in particular with 1-hour post-load plasma glucose levels.MethodsWe enrolled 300 consecutive Caucasian hypertensive never… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 46 publications
2
12
0
Order By: Relevance
“…Another important finding in this study is the improvement in glucose homeostasis parameters in both groups after 12 months of nutritional therapy, with the most impressive improvement observed in the VLCKD group. Of note, HOMA was another independent predictor of the variation of serum 25(OH)D concentrations after weight loss in the whole study population, confirming previously published data, which demonstrated that vitamin D status affects glucose and insulin homeostasis [30].…”
Section: Discussionsupporting
confidence: 87%
“…Another important finding in this study is the improvement in glucose homeostasis parameters in both groups after 12 months of nutritional therapy, with the most impressive improvement observed in the VLCKD group. Of note, HOMA was another independent predictor of the variation of serum 25(OH)D concentrations after weight loss in the whole study population, confirming previously published data, which demonstrated that vitamin D status affects glucose and insulin homeostasis [30].…”
Section: Discussionsupporting
confidence: 87%
“…Additionally, the cholesterol efflux capacity was significantly associated with fasting glucose and the Matsuda index, a validated measure of insulin sensitivity. 20,21 This result supports the hypothesis that the conditions resulting from insulin resistance detrimentally influence cholesterol efflux capacity. A study conducted by Laakso and colleagues demonstrated that the serum HDL and HDL 2 levels in noninsulin-dependent diabetics were lower in comparison to the nondiabetic control subjects.…”
Section: Discussionsupporting
confidence: 82%
“…The Matsuda index is a dynamic measurement of insulin resistance and is strongly related to the ideal measurement of the euglycemic hyperinsulinemic clamp. 20,21 The fasting lipid profile included total cholesterol, HDL-C, directly measured low-density lipoprotein (LDL-C) cholesterol, and total triglycerides by an enzymatic, colorimetric assay as previously reported. 22 Lipoprotein particle concentration and diameters were measured using an automated NMR.…”
Section: Study Cohortmentioning
confidence: 99%
“…They were also found to be at high risk for the development of chronic kidney disease, ultrasonographic diagnosis of non‐alcoholic fatty liver disease, increased vascular stiffness, and early carotid atherosclerosis than those with IFG or NGT and 1‐hour PG < 155 mg/dl (8.6 mmol/L). Sub‐analyses demonstrated an association between NGT individuals and a 1‐hour PG ≥155 mg/dl (8.6 mmol/L) with elevated liver enzymes, adverse atherogenic profile, reduced vitamin D concentrations, decreased insulin clearance, insulin sensitivity and reduced β‐cell function, unfavourable inflammatory profile, and whole blood viscosity …”
Section: Introductionmentioning
confidence: 99%